Myositis in Scrub Typhus: Atypical Presentation - Parth Sharma; Sahil Attri; Aprajita Garg; Karan Sharma (JK Science)
Scrub infection is caused by Orientia tsutsugamushi, due to the bite of a chigger. It has a wide presentation, including febrile illness, ARDS (acute respiratory distress syndrome), and encephalopathy. However, we report a rare case of myositis in Scrub Typhus.